Enhancing EFL Students’ Writing Performance through Process-Based Instruction: Evidence from Ethiopian High School - Kifle Desalegn; Alemu Hailu (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Developing writing performance remains a challenge for many language learners, particularly when the instructions are predominantly teacher-centered and form-oriented. The study aimed to examine the effectiveness of process-based instruction on grade ten students’ writing performance. This study employed a quasi-experimental design, as it was well-suited for comparing two intact groups. These sections were purposively selected from 10 sections of grade ten and subsequently assigned randomly to experimental (10C) and control (10D) groups, after pre-test. To ensure triangulation and strengthen validity and reliability, the study applied mixed methods comprising tests, questionnaires, and interviews. Questionnaires were administered to ten teachers and interviews to four, to examine their perceptions of the instruction. Quantitative data from paragraph tests and questionnaires were analyzed using a t-test and descriptive statistics, respectively, whereas qualitative data from interviews were examined thematically. The findings revealed a statistically significant improvement in writing performance for the experimental group (t (39) = -23.213, p < .000), supported by a strong effect size (Cohen’s d = 1.17). Moreover, process-based instruction fostered social interaction among students and develop their motivation to write, facilitating collaborative writing practices. These results underscore process-based instruction's substantial impact on learning outcomes and emphasize stakeholders to provide professional training and equip teachers with practical skills to implement this instruction effectively and to integrate it into the language curriculum. Integration of such instruction into language education system is essential for promoting students’ participation, enhancing creativity, collaborative learning, and exchanging feedback, thereby contributing to improved writing performance.